Sales promotion - Mullin, Roddy (Henry Stewart Talks, 2012)
Marketing processes, How promotions can sway customers, How to succeed with the use of promotions, How promotions work and what to look out for, The law and regulations regarding promotions
Updated at 2020/03/30